Making Human Rights Law Work in Dismissal Cases: Insights from the Martinus Masa Dorita v. PT Musim Mas Case - Hadi, Sahid; Erlangga, Vania Lutfi Safira (Fakultas Hukum Universitas Islam Indonesia, 2025)
The nature of private law is strongly embedded in dismissal cases. For this reason, human rights standards are rarely applied in the settlement of such cases in court. However, the Martinus Masa Dorita v. PT Musim Mas case demonstrated a different practice. Particularly in the court of first instance, the judges explicitly considered human rights law, resulting in a judgment that contrasted with the parties’ claims. In spite of the fact that the Supreme Court annulled the decision of the court of first instance, the presence of human rights argumentation in the journey of the case remains important to explore. By analyzing judges’ reasoning in the court decisions for the case, this doctrinal legal research developed a legal methodology for the application of human rights standards in dismissal cases. We found that the judges have made human rights standards work by reinterpreting pre-existing employment law provisions that govern employee-employer relations using an impact-oriented reasoning method. This work contributes to a greater understanding of how judges can put human rights law to work when developing their reasoning for dismissal cases. Based on the case, human rights-based reasoning enables judges to provide vigorous protection of workers’ human rights and deliver substantive justice. We argue that human rights considerations enable courts to create equilibrium in unequal employee-employer relations.